2009
DOI: 10.1111/j.1369-7625.2008.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary‐care patients’ expectations and experiences of online cognitive behavioural therapy for depression: a qualitative study

Abstract: Objective To explore expectations and experiences of online cognitive behavioural therapy (CBT) among primary-care patients with depression, focusing on how this mode of delivery impacts upon the therapeutic experience.Design Qualitative study, using repeat semi-structured interviews with patients before and after therapy. The study was conducted in parallel with a randomized controlled trial examining the effectiveness and cost-effectiveness of online CBT for patients with depression.Participants Twenty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
182
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(202 citation statements)
references
References 28 publications
17
182
2
1
Order By: Relevance
“…In summary, the results indicated that the participants' experiences on the whole were comparable with previous findings within qualitative research of internet-based guided self-help treatment (Beattie, Shaw, Kaur, & Kessler, 2009;Bendelin et al, 2011;Khan, Bower, & Rogers, 2007;Macdonald, Mead, Bower, Richards, & Lovell, 2007). What seemed to be unique in this study was that the smartphone-based treatment felt more accessible and present in the participants' everyday lives.…”
Section: Resultssupporting
confidence: 78%
“…In summary, the results indicated that the participants' experiences on the whole were comparable with previous findings within qualitative research of internet-based guided self-help treatment (Beattie, Shaw, Kaur, & Kessler, 2009;Bendelin et al, 2011;Khan, Bower, & Rogers, 2007;Macdonald, Mead, Bower, Richards, & Lovell, 2007). What seemed to be unique in this study was that the smartphone-based treatment felt more accessible and present in the participants' everyday lives.…”
Section: Resultssupporting
confidence: 78%
“…Most papers originated in Europe (n = 18, including 11 in the UK), followed by the USA (n = 7), Canada (n = 3) and Australia (n = 1). The evidence base addressed a wide range of conditions, some of them relevant to the Healthlines study, particularly depression, 98,99 hypertension 100 and online counselling. 101 We identified three themes from these papers -perceived access, care and symptom management and technologies -and then focused on the question of which professionals or agencies should deliver services, as this was of particular interest to the Healthlines study in terms of designing the subsequent RCT.…”
Section: Resultsmentioning
confidence: 99%
“…97,[102][103][104] Rural patients with moderate depression perceived an improvement in access from using telehealth. 99 Patients reported advantages of online interventions for mental health and behavioural problems, including convenience, access and anonymity, 98,99 but these were often balanced by concerns about lack of closeness and therapist trust, privacy and confidentiality fears and lack of visual cues. Patients shown a video of a Home Telecare Management System were positive, mentioning perceived benefits of less travel time and fewer medical visits, but there were some concerns about whether or not it could be used by some patients with disabilities.…”
Section: Perceived Accessmentioning
confidence: 99%
“…Further, PRPs' concerns regarding limitations of not being able to personalise the content of the intervention are consistent with wider research [14]. Moreover, the lack of personal interaction with an e-therapist has been highlighted [22], with participants reporting difficulties developing a relationship with an etherapist online in the absence of face-to-face contact [23]. However, the inclusion of a video call at the beginning of the intervention may overcome these concerns.…”
Section: Process Evaluationmentioning
confidence: 89%